Semantische Variabilitaet der russischen politischen Lexik im zwanzigsten Jahrhundert - Becker, Joern-Martin (Slavistische Beitraege, 2001)
The aim of the research is to demonstrate, using the example of the field of semantics, that the political lexicism of the Russian language of the twentieth century, despite its variability, forms a historical and supra-ideological unity, which continues to be closely linked to the lexicon of a general discourse. The following questions set the framework for the analysis: 1) How uniform and complex is the system of meanings in the political lexic of the Russian language in the twentieth century; 2) how continuous has the semantic development of this vocabulary area been; 3) what general regularities has the development process followed; 4) how does the political lexicon relate to the overall lexical-semantic system of the Russian language or to the overall system of international political lexicism?